Influence of rock mass properties and powder factor on the fractal dimension of the natural rock mass blocks during blasting - Ajay Pratap Singh Tomar; Suman Panthee; Sanjaya Dahal; Sandesh Pandey (Discover Geoscience)
Abstract The rock mass fragmentation in discontinuous rock mass is a concern issue in rock mass blasting. The purpose of the study is to find out the influencing parameters of rock mass and blast design in degree of fragmentation of natural block during blasting. The fragmentation conditions were evaluated by block fragmentation method in three different rock types. Blasted block size reduction from in-situ block size distribution (ISBD) to blasted block size distribution (BBSD) were analyzed based on modified Kuz-Ram models and other empirical models which were used to predict D50 of the blocks. Similarly, blastability index (BI), blastability designation (BD), and Fragmentation index (FI) were used to analyzed fractal dimension of block (i.e. volume reduction) from in-situ to blasted rock blocks where average reduction amount in block fragmentation were found 80.3%, 76.41% and 60.14% in Gneiss, Phyllite, and Metasandstone respectively. The result of this study revealed that the blastability and fragmentation index of rock mass depends on in-situ block size, rock mass strength, and powder factor used during blasting. Based on the outcome of the study rock fragmentation and fragmented block size can be predicted by understanding of the discontinuity characteristics of the rock mass along with rock mass class and powder factor of that blasting. Therefore, desired level of block fragmentation, blastability and fragmentation index of blasting rock mass can be got by modifying the blasting design according to the natural block size and rock mass strength of the rock mass.